Psychological interventions for ICD-11 complex PTSD symptoms: systematic review and meta-analysis. Issue 11 (12th March 2019) - Karatzias, Thanos; Murphy, Philip; Cloitre, Marylene; Bisson, Jonathan; Roberts, Neil; Shevlin, Mark; Hyland, Philip; Maercker, Andreas; Ben-Ezra, Menachem; Coventry, Peter; Mason-Roberts, Susan; Bradley, Aoife; et al.
Abstract: Background: The 11th revision to the WHO International Classification of Diseases (ICD-11) identified complex post-traumatic stress disorder (CPTSD) as a new condition. There is a pressing need to identify effective CPTSD interventions. Methods: We conducted a systematic review and meta-analysis of randomised controlled trials (RCTs) of psychological interventions for post-traumatic stress disorder (PTSD), where participants were likely to have clinically significant baseline levels of one or more CPTSD symptom clusters (affect dysregulation, negative self-concept and/or disturbed relationships). We searched MEDLINE, PsycINFO, EMBASE and PILOTS databases (January 2018), and examined study and outcome quality. Results: Fifty-one RCTs met inclusion criteria. Cognitive behavioural therapy (CBT), exposure alone (EA) and eye movement desensitisation and reprocessing (EMDR) were superior to usual care for PTSD symptoms, with effects ranging from g = −0.90 (CBT; k = 27, 95% CI −1.11 to −0.68; moderate quality) to g = −1.26 (EMDR; k = 4, 95% CI −2.01 to −0.51; low quality). CBT and EA each had moderate–large or large effects on negative self-concept, but only one trial of EMDR provided useable data. CBT, EA and EMDR each had moderate or moderate–large effects on disturbed relationships. Few RCTs reported affect dysregulation data. The benefits of all interventions were smaller when compared with non-specific interventions (e.g. befriending). Multivariate meta-regression suggested childhood-onset trauma was associated with a poorer outcome. Conclusions: The development of effective interventions for CPTSD can build upon the success of PTSD interventions. Further research should assess the benefits of flexibility in intervention selection, sequencing and delivery, based on clinical need and patient preferences.